Investigation of LSM/8YSZ cathode within an all-ceramic SOFC, Part II: Optimization of performance and co-sinterability. Issue 10 (August 2020) - Harboe, S.; Lupetin, P.; Guillon, O.; Menzler, N.H.
Abstract: This paper focuses on the cathode and current collector layers of a co-sintered, all-ceramic solid oxide fuel cell (SOFC) concept. Challenges to reach good electrochemical performance have to be overcome, due to more demanding manufacturing conditions, including a relatively high co-sintering temperature. Master sintering curves show that the sintering activity of lanthanum strontium manganite (LSM) is significantly higher than that of 8-mol% yttria stabilized zirconia (8YSZ). By applying a double-layered cathode and a current collector with optimized microstructures the best electrochemical performance of the cathode is 0.26 Ω cm 2 at 800 ° C, evaluated from polarization resistances of 8YSZ electrolyte-supported symmetric cells post-sintered at 1150 ° C < T < 1250 ° C. The cathode and current collector materials are adapted to fit the co-sintering process by adjustment of the paste compositions. Half-cells consisting of silicate mechanical support, LSM current collector, LSM mixed with 8YSZ composite cathode and 8YSZ electrolyte are co-sintered porous and defect-free at 1150 ° C < T < 1250 ° C.